Asymptomatic nodule on face: Dermoscopic and histopathological clue for diagnosis - Joshi, Anisha; Thapa, Deeptara Pathak (Nepal Journal of Neuroscience, 2020)
Schwannomas/ neurilemmomas are benign tumors of nerve sheath arising from Schwann cells that form myelin sheath around peripheral nerves. They are usually solitary, slow growing and encapsulated lesions. Head and neck are the common sites. We report a case of a 38 years old Nepalese female who had presented with a solitary asymptomatic, slow growing nodule on the left side of the chin for the last three years. Dermoscopy of the lesion revealed arborizing vessels with brownish pigmentation overlying a whitish to pinkish background. Complete excision of the lesion was performed. Histopathological evaluation of the lesion revealed schwannoma. Though schwannomas are a rare diagnosis, they should be considered as a differential diagnosis of any unilateral, asymptomatic, slow growing nodule in the head and neck region. Dermoscopy is a useful tool which helps to differentiate schwannoma from other lesions. Histopathology is the gold standard for diagnosis and the treatment of choice is surgical excision.